First principle study on the predicted phase transition of MN (M = Zr, La and Th). (30th May 2019) - Li, Y L; Cai, J; Mo, D; Wang, Y D
Abstract: First principle (FP) calculations were performed to systematically study the structural properties of ZrN, LaN and ThN with GGA correction. The ground state properties, wave velocities and Debye temperature of B 1, P 63 / mmc, Pnma and B 2 phase in ZrN, LaN and ThN were investigated and agree well with other theoretical and experimental results. More importantly, some novel phases are predicted in these materials, i.e. with the increasing pressure the phase transition sequence in ZrN and ThN is found to be B 1  →   P 63 / mmc   →   B 2 phase, while in LaN, the sequence of B 1  →   Pnma   →   B 2 is observed. Furthermore, our calculated elastic properties also confirm the prediction of phase transition under high pressure. These phase transitions arise from the optical phonon softening of B 1 at around X, M and G points of Brillouin zone and P 63 / mmc (or Pnma ) structure at around G, and H – K points.